Nutritional analysis of cultivated mushrooms of India - KUMAR, SANJEEV; SAGAR, ANAND (The Indian Journal of Agricultural Sciences, 2023)
The fruiting bodies of the latest strains of edible mushrooms were obtained from the ICAR-Directorate of Mushroom Research, Solan, Himachal Pradesh during 2020–21. The objective of the study was to evaluate the nutritional values including carbohydrates, proteins, fats, dietary fiber, energy, moisture and ash contents of cultivated mushrooms with the view to increase awareness regarding benefits of mushrooms. The samples were analyzed for different parameters from Punjab Biotechnology Incubator, Mohali, India. The results showed 15.27 to 38.75% proteins, 0.84 to 3.88% lipids, 39.33 to 69.60% carbohydrates, 30.22 to 40.48% dietary fibers, 319.9 Kcal/100 g to 363.1 Kcal/100 g energy, 87.02 to 92.44% moisture and 6.75 to 9.5% ash content. The results of the present study also showed closeness to the results of the previous studies.